A new class of bioactive glasses: Calcium–magnesium sulfophosphates. Issue 8 (2nd October 2013) - Bassett, David C.; Meszaros, Robert; Orzol, Dominik; Woy, Michel; Ling Zhang, Yu; Tiedemann, Kerstin; Wondraczek, Lothar; Komarova, Svetlana; Barralet, Jake E.
Abstract Low‐melting ionic sulfophosphate glasses from the system P2O5‐SO4‐MO‐Na2O (M = Zn2+, Ca2+ or Mg2+) have been previously shown by us to allow tuneable aqueous dissolution and also enable processing temperatures well below 400°C. Sulfate ions are extremely safe for use in the body as decades of use of calcium sulfate bone grafts testifies and there is no known limit on their adult oral toxicity. This glass system therefore offers great potential for use as biomaterials, especially in organic–inorganic hybrid systems such as glass‐polymer composites for tissue engineering or drug encapsulation and delivery applications. A compositional region was identified where stable sulfophosphates of the type P2O5‐SO4‐(Ca, Mg, Zn)O‐Na2O can be fabricated. For these glasses, the viscosity‐temperature‐dependence, glass transformation temperatures (Tg) and the onset of crystallization were evaluated as the primary processing parameters. As a first step in exploring their potential as a biomaterial, in this study we examine the bioactivity of several compositions of these glasses using fibroblast, monocyte, and osteoclast cell culture models to determine cellular responses in terms of attachment, proliferation, differentiation, and toxicity. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2842–2848, 2014.